Lectures on Elliptic Partial Differential Equations - Ambrosio, Luigi (Lecture Notes (Scuola Normale Superiore) ;, 2018)
The book originates from the Elliptic PDE course given by the first author at the Scuola Normale Superiore in recent years. It covers the most classical aspects of the theory of Elliptic Partial Differential Equations and Calculus of Variations, including also more recent developments on partial regularity for systems and the theory of viscosity solutions.